Invasive and Noninvasive Group A Streptococcal Isolates with Different speA Alleles in The Netherlands: Genetic Relatedness and Production of Pyrogenic Exotoxins A and B - Mascini, Ellen M. (American Society for Microbiology, 1999)
Streptococcal pyrogenic exotoxin A (SPE-A) and SPE-B have been implicated in the pathogenesis of severe group A streptococcal (GAS) disease. We studied 31 invasive GAS strains including 18 isolates from patients with toxic shock syndrome and 22 noninvasive strains isolated in The Netherlands between 1994 and 1998. These strains were associated with the different allelic variants of the gene encoding SPE-A. We selected endemic strains with speA-positive M and T serotypes: speA2-associated M1T1 and M22-60T12 strains, speA3-associated M3T3 strains, and speA4-associated M6T6 strains. Since speA1-positive isolates were not frequently encountered, we included speA1 strains of different serotypes. The GAS strains were compared genotypically by pulsed-field gel electrophoresis and phenotypically by the in vitro production of SPE-A and SPE-B. All strains within one M and T type appeared to be of clonal origin. Most strains produced SPE-A and SPE-B, but only a minority of the speA4-positive isolates did so. Among our isolates, speA1- and speA3-positive strains produced significantly more SPE-A than speA2- and speA4-carrying strains, while SPE-B production was most pronounced among speA1- and speA2-containing strains. There was a marked degree of variability in the amounts of exotoxins produced in vitro by strains that shared the same genetic profile. We conclude that the differences in the in vitro production of SPE-A and SPE-B between our selected strains with identical M and T types were not related to either genetic heterogeneity or the clinical course of GAS disease in the patient from whom they were isolated.